Manajemen Operasi Produksi: Pencapaian Sasaran Organisasi Berkesinambungan,-- Edisi 3 - ASSAURI, Sofjan (Rajawali, 2015)
Manajemen Operasi Produksi: Pencapaian Sasaran Organisasi Berkesinambungan,-- Edisi 3